Developing the Chinese version of the Index of Sojourner Social Support: the roles of socio-emotional and instrumental support in internal migrant university students - Fu, Hanzhi (Frontiers in Psychology, 2025)
IntroductionThis study aims to validate the Index of Sojourner Social Support (ISSS)—a widely-used scale for measuring social support in cross-cultural (including cross-national and internal) migrations—in Chinese contexts among internal migrant university students and explore how such support can facilitate their psychological adjustment.MethodsOne thousand six hundred ninety-two university students who migrated from all around China to the city of Shanghai participated in this study. The ISSS was translated according to strict procedures. Item analysis, confirmatory factor analysis (CFA), reliability analysis, measurement equivalence test, criterion validity test, and incremental validity test of the Chinese version of the ISSS (ISSS-C) were carried out.ResultsThe ISSS-C generated by this study had two dimensions (socio-emotional support and instrumental support) of 18 items. The model fit was excellent (χ2/df = 5.64, CFI = 0.96, TLI = 0.95, SRMR = 0.03, and RMSEA = 0.06). The McDonald's omegas for its two subscales were both 0.96. The measurement equivalence of the ISSS-C and criterion validity were also excellent. Instrumental support significantly influenced students' psychological adjustment to the host culture, partially establishing incremental validity for the scale.DiscussionThe ISSS-C exhibits good psychometric properties and is appropriate for measuring social support perceived by migrant university students in Chinese cultural contexts. Further, instrumental support can assist them in psychologically adjusting well to local environments.